Stališča izvajalcev nujne medicinske pomoči o uporabnosti triažnega kartona - Sedej, Tilen (Obzornik zdravstvene nege, 2014)
Introduction: Categorized victims of a mass casualty event need to be labeled to help other participants in the rescue chain in sorting of patients into priority groups according to their needs and the resources available. The aim of the study was to determine the usability of triage tags employed in mass-casualty incidents in the Republic of Slovenia defined in the Law on Emergency Medical Services Act. Methods: The data were collected through a structured questionnaire. The research sample included seven units of emergency medical services (EMS) at the primary level of health care of Upper Carniola (Gorenjska region). Of 136 questionnaires distributed among EMS providers, 94 were properly completed and returned. The data obtained were processed by descriptive and bivariate statistical methods. Results: The present results are significant in at least two respects. It has been established that the respondents are not confident in their ability to use the required triage tag (x = 3.26) and that the required triage tag is not completely unusable triage tool regardless of its drawbacks (x = 3.43). The respondents are of the opinion that the triage tag should have the option of a colorcoding scheme (x = 4.00) and a possibility to modify the patient's category if so required during the course of treatment (x = 3.99). Opinions vary in dependence on the length of experience of EMS providers (p = 0.05) and their competence to perform and document triage (p = 0.04). The agreement with both statements is significantly more pronounced in respondents with seniority. Discussion and conclusion: It is necessary to improve the competence of EMS providers in the use of the required triage tags in mass casualty management. In Slovenia, a type of triage tag which will accord with the current trends in intervention in mass casualty situations is needed. Additional research is therefore required to secure better emergency and disaster preparedness and response.
Keywords: emergency medical service; izredne razmere; major incidents; mass casualty incident; množične nesreče; nujna medicinska pomoč; triage; triaža